Caracterização do uso da fauna cinegética em aldeias das etnias Wayana e Aparai na terra indígena parque do Tumucumaque, Pará - VELTHEM LINKE, Iori Leonel Arnoldo Hussak Van (Universidade Federal do Pará, 2013)
The game is very important for the maintenance of traditional ways of life of indigenous peoples in the Amazon. However, when the game is not made in a sustainable way the pressure can lead to local extinctions and imbalances in the ecosystem. This study aims to characterize the use of wildlife hunting in two villages of ethnic Wayana and Aparai who lives in Parque Indígena do Tumucumaque, northern of Pará State. Were tracked and interviewed 29 hunters in 60 days of data collection. The interviews have raised 45 species of mammals occurring in the area and also the main game species with their respective seasons of hunting. Altogether 219 animals were hunted from 35 different species, totaling 2,558 kg of biomass. The species was hunted more Tayassu peccary (n = 50; 1,350 kg), second was Ateles paniscus (n = 30, 261 kg). The most hunted bird was Crax Alector (n = 18, 58.5 kg), and the green lizard Iguana iguana was the most hunted reptile (n = 18, 37 kg). Of these, all were within the expected average weights. Only for I. iguana statistical difference was observed in sex ratio, and all the A. paniscus killed were females. The curves of survivalship of the most hunted mammals, T. peccary, A. paniscus, Cebus apella (n = 16) and Cuniculus paca (n = 12) points to a sharp withdrawal of adult and senile animals. The favorite game species were, in descending order, A. paniscus, C. apella, C. paca, T. peccary, Pecari tajacu, Tapirus terrestris, Alouatta macconnelli, Mazama americana, C. Alector and Psophia crepitans. By the hunting methods of active-selective and non-selective-opportunistic were recorded the same number of animals hunted. Due to the hunting of large mammals, the largest amount recorded opportunistic forms of biomass harvested (1590 kg), while selective methods focused primates and birds, totaling 968 kg. Due cultural issues, the Wayana and Aparai hunters seek animals when they are fat. They rarely hunt animals outside the species hunting seasons. The activity of fishing yielded 1211.7 kg of 44 morphospecies. The game was about 2/3 of all biomass consumed. Meals based on game meat were more extensive and yielded more protein than meals with fish. The per capita daily consumption of game was 104.37 g and 22.44 g of fish. The area used to hunt of the two villages was estimated at 518.73 km ². The analysis of sustainability of hunting suggests that only C. apella and A. paniscus are being over-exploited.